LOGICAL MODEL, A PRECEDING STEP FOR THE QUALITY OF THE DECISION-MAKING - Canco, Irina (European Scientific Journal, ESJ, 2015)
The competition challenges make businesses face with the different nature problems. The consequences of this reality are reflected on the business perspective with deep changes in their status and their activity. In this context, the development of successful business, in a certain degree, is conditioned by decision-making. The decision-making in business is an important activity and, as such, it has attracted the researchers’ attention for a long time. This is reflected in literature. The literature refers to the decisionmaking starts in early periods. But if we consider that the decision-making is a very important activity, researchers still continue to develop their decisionmaking theories which are based on the old theories. The theories of decision making in today’s times are enriched as a result of their continued evolution. So there is a numerous literature where various aspects of decision making are treated separately, or linked and coordinated with each other. This paper will treat some problems of decision-making by focusing on presenting a comprehensive picture of a logical decision-making model. Also it will be presented chronologically and through relevant perspectives.